Critical care: A concept analysis - Martin Christensen; Mining Liang (Elsevier, 2023)
Objective: The terms critical care and the Intensive Care Unit (ICU) are often used interchangeably to describe a place of care. Defining critical care becomes challenging because of the colloquial use of the term. Using concept analysis allows for the development of definition and meaning. The aim of this concept analysis is to distinguish the use of the term critical care to develop an operational definition which describes what constitutes critical care. Method: Walker and Avant's eight-step approach to concept analysis guided this study. Five databases (CINAHL, Scopus, PubMed, ProQuest Dissertation Abstracts and Medline in EBSCO) were searched for studies related to critical care. The search included both qualitative and quantitative studies written in English and published between 1990 and 2022. Results: Of the 439 papers retrieved, 47 met the inclusion criteria. The defining attributes of critical care included 1) a maladaptive response to illness/injury, 2) admission modelling criteria, 3) advanced medical technologies, and 4) specialised health professionals. Antecedents were associated with illness/injury that progressed to a level of criticality with a significant decline in both physical and psychological functioning. Consequences were identified as either death or survival with/without experiencing post-ICU syndrome. Conclusion: Describing critical care is often challenging because of the highly technical nature of the environment. This conceptual understanding and operational definition will inform future research as to the scope of critical care and allow for the design of robust evaluative instruments to better understand the nature of care in the intensive care environment.